Metode Fatwa MPU (Majelis Permusyawaratan Ulama) Aceh - Nurkhalis muchtar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Fatwa is a process of providing legal certainty to issues that arise which are asked of the mufti. The people's need for fatwas began at the beginning of the development of Islam, which was marked by the presence of the Prophet as the first figure giving fatwas. In Islam, fatwas have an important position, so those who give fatwas must have adequate competence and scientific capacity. As far as research is concerned, no work has been found that specifically examines the fatwa method of the Aceh Ulama Consultative Council, bearing in mind that the fatwa issued by the Aceh Ulama Consultative Assembly has a great influence on Acehnese society. This research was conducted to answer two big questions which became the formulation of the problem, namely how is the MPU Aceh fatwa method and its application? How does the Aceh MPU fatwa method relate to the fatwa on the determination of the Ghair Mu'tabar book? In answering these two big questions, the researcher uses qualitative descriptive research using two approaches, namely library research which will examine the fatwa in depth and the history of the Aceh MPU and its fatwas. The second approach is with field research, to examine the extent to which the effect of the fatwa of the Ghair Mu'tabar book is on society. The theoretical framework used in this study is to use the theory of Islamic scholars and scientists who write about religious fatwas. This research is expected as an effort to understand the process of presenting fatwas that are right on target, so that stability can be created in life, the realization of justice, benefit and prosperity in human life in this world and in the hereafter.